Successful conservative management of left ventricular assist device candidates. (15th November 2022) - Havakuk, Ofer; Hochstadt, Aviram; Sadon, Sapir; Laurel Perl, Michal; Sadeh, Ben; Milwidsky, Assi; Ran Sapir, Orly; Granot, Yoav; Lupu, Lior; Levi, Erez; Farkash, Ariel; Ben Gal, Yanai; et al.
Abstract: Aims: Clinical trials comparing LVADs vs. conservative therapy were performed before the availability of novel medications or used suboptimal medical therapy. This study aimed to report that long‐term stabilization of patients entering a left ventricular assist device (LVAD) programme is possible with the use of aggressive conservative therapy. This is important because the excellent clinical stabilization provided by LVADs comes at the expense of significant complications. Methods and results: This study was a single‐centre prospective evaluation of consecutive patients with advanced heart failure (HF) fulfilling criteria for LVAD implantation based on clinical and echocardiographic characteristics, cardiopulmonary exercise test, and right heart catheterization results. Their initial therapy included inotropes, thiamine, beta‐blockers, digoxin, spironolactone, hydralazine, and nitrates followed by the introduction of novel HF therapies. Coronary revascularization and cardiac resynchronization therapy were performed when indicated, and all patients were closely followed at our outpatient clinic. During the study period, 28 patients were considered suitable for LVAD implantation (mean age 63 ± 10.8 years, 92% men, 78% ischaemic, median HF duration 4 years). Clinical stabilization was achieved and maintained in 21 patients (median follow‐up 20 months, range 9–38 months). Compared with baseline evaluation, cardiac index increased from 2.05 (1.73–2.28) to 2.88 (2.63–3.55) L/min/m 2, left ventricular end‐diastolic diameter decreased from 65.5 (62.4–66) to 58.3 (53.8–62.5) mm, and maximal oxygen consumption increased from 10.1 (9.2–11.3) to 16.1 (15.3–19) mL/kg/min. Three patients died and only four ultimately required LVAD implantation. Conclusions: Notwithstanding the small size of our cohort, our results suggest that LVAD implantation could be safely deferred in the majority of LVAD candidates.